Synthesis of Poly(hydroxamic acid) Ligand from Polymer Grafted Khaya Cellulose for Transition Metals Extraction - Lutfor, M. R.; Manda, Bablu Hira; Sarkar, Shaheen M.; Nor Asiken, Abdul Wahab; M. M., Yusoff; Sazmal E., Arshad; Musta, Baba (The Korean Fiber Society, 2016)
A cellulose-graft-poly(methyl acrylate) was synthesized by free radical initiating process and the ester functional groups were converted into the hydroxamic acid ligand. The intermediate and final products are characterized by FT-IR, FESEM, HR-TEM and XPS technique. The pH of the solution acts as a key factor in achieving optical color signals of metalcomplexation. The reflectance spectra of the[Cu-ligand]n+ complex was found to be a highest absorbance at 99.8 % at pH 6 and it was increased upon increasing of Cu2+ ion concentrations and a broad peak at 700 nm was observed which indicated the charge transfer (π-π transition) metals-Cu complex. The adsorption capacity of copper was found to be superior (336 mg g-1)rather than other transition metals such as Fe3+, Co3+, Cr3+, Ni2+, Mn2+ and Zn2+ were 310, 295, 288, 250, 248 and 225 mg g-1, respectively at pH 6. The experimental data of all metal ions fitted significantly with the pseudo-second-order rate equation. The transition metal ions sorption onto ligand were well fitted with the Langmuir isotherm model (R2>0.99), which suggested that the cellulose-based adsorbent known as poly(hydroxamic acid) ligand surface is homogenous and monolayer. The reusability of the poly(hydroxamic acid) ligand was checked by the sorption/desorption process up to ten cycles without any significant loss in its original sensing and removal performances.